Legal Reforms on Water and Coastal Management to Prevent Conversion into Property Companies - Faradila Arrahma; Azzahra Amalia Wijaya Wijaya; Devita Antikasari; Niken Huniarni; Febrilia Wulan Nanta (Decova Law Journal, 2025)
Resource management in Indonesia’s coastal areas is facing intense controversy, particularly regarding the Pantai Indah Kapuk Dua (PIK) project in Tangerang, Banten. This project, developed by a consortium of the Salim Group and Agung Sedayu Group, was established in a coastal zone rich in ecological and historical value, but has had detrimental effects on the environment and local communities. The construction of PIK 2 proceeded without community participation, resulting in fishermen losing their livelihoods and an increased potential for flooding due to an inadequate drainage system. Although the 1945 Constitution mandates that the use of natural resources be aimed at the prosperity of the people, in practice, this project prioritizes investors' interests, violates human rights, and triggers social friction. Land conversion without sustainability principles demonstrates weak governance and disregard for environmental law. This study emphasizes the importance of legal reform through flexible regulations, local community involvement, fair land governance, and protection of public access. Using normative methods, a legislative approach, and case studies, this research calls for comprehensive environmental assessments and information transparency in coastal zone management. Without an inclusive and sustainable approach supported by law, coastal development such as PIK 2 will only exacerbate social inequality and environmental degradation.